If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4t(5t + -4t) = 0 Combine like terms: 5t + -4t = 1t 4t(1t) = 0 Remove parenthesis around (1t) 4t * 1t = 0 Reorder the terms for easier multiplication: 4 * 1t * t = 0 Multiply 4 * 1 4t * t = 0 Multiply t * t 4t2 = 0 Solving 4t2 = 0 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Divide each side by '4'. t2 = 0 Simplifying t2 = 0 Take the square root of each side: t = {0}
| 5/2x=0 | | 65ab^3-45a^2b^2=0 | | 16=9x+2-2x | | 5.4x=7.02 | | 5n^2-16n=-3 | | 7x-8=x+7 | | 0.15(x+10)=8x+20 | | 5-2a=5a-2 | | -1(3x+4)-4r=-2(4r-3)+2 | | 2x+5=6x-9 | | x+-2x+4=3 | | 16+5a=56 | | x^2+4x+4y^2=0 | | 6x+14=5x+12 | | 3(m^2+10m+23)=0 | | r^2+3r=10 | | 7a-7+6a=10-4a | | 3x^2+11x-1-x^3=0 | | y=-2(x+3)2+2 | | x/2=20/10 | | 10t+3(1-4t)= | | x-59=-24 | | A=3.14r*2(5) | | 8m=-14-30 | | x^(2/3)e^x | | 6.5x=7.8 | | 16-4=3x+8-6 | | 4x+4+2x+1= | | .2x+104.8=102 | | 7t+3(1-5t)= | | 4x^2-36x=-85 | | 6+6+3-(-2)= |